Biological biomarkers in muscle diseases relevant for follow-up and evaluation of treatment - Stemmerik, Mads G; Tasca, Giorgio; Gilhus, Nils Erik; Servais, Laurent; Vicino, Alex; Maggi, Lorenzo; Sansone, Valeria; Vissing, John (Brain (London, England : 1878), 2025)
Muscle diseases cover a diverse group of disorders that, in most cases, are hereditary. The rarity of the individual muscle diseases provides a challenge for researchers when wanting to establish natural history of the conditions and when trying to develop diagnostic tools, therapies, and outcome measures to evaluate disease progression. With emerging molecular therapies in many genetic muscle diseases, as well as biological therapies for the immune-mediated diseases, biological biomarkers play an important role in both drug development and evaluation. In this review, we focus on the role of biological biomarkers in muscle diseases and discuss their utility as surrogate end points in therapeutic trials. We categorize these as either (i) disease unspecific markers; (ii) markers of specific pathways that may be used for more than one disease; or (iii) disease-specific markers. We also propose that evaluation of specific therapeutic interventions benefits from biological markers that match the intervention.